2016
DOI: 10.5551/jat.31575
|View full text |Cite
|
Sign up to set email alerts
|

Reduced T-Cell Thymic Export Reflected by sj-TREC in Patients with Coronary Artery Disease

Abstract: Aim:Immunologic dysfunction was recently found to be one of the most important mechanisms underlying the initiation and development of atherosclerosis. Thymus involution can contribute to immune disturbance and disequilibrium of T-cell subsets. This study aimed to explore whether recent thymic emigration (RTE) is impaired in patients with coronary artery disease (CAD). Methods: Content of signal-joint T cell receptor excision circles (sj-TREC) in T lymphocytes, a molecular marker of RTE, was assessed among CAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 59 publications
(70 reference statements)
1
14
0
Order By: Relevance
“…Therefore, there are reasons to believe that the thymus Foxn1 may be involved in the process of atherosclerosis. In previous studies, the atrophy of thymus organs in patients with coronary heart disease has been confirmed 26 , yet the specific altering of thymus function has not been clearly revealed.…”
Section: Aging and Atherosclerosismentioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, there are reasons to believe that the thymus Foxn1 may be involved in the process of atherosclerosis. In previous studies, the atrophy of thymus organs in patients with coronary heart disease has been confirmed 26 , yet the specific altering of thymus function has not been clearly revealed.…”
Section: Aging and Atherosclerosismentioning
confidence: 94%
“…Our previous study showed that there was a decline in thymus function in atherosclerotic patients 26 . Therefore, the thymus may be involved in the process of atherosclerosis.…”
Section: Introductionmentioning
confidence: 94%
“…An important parameter that measures thymopoiesis is the generation of T cells as recent thymic emigrants (RTEs), which reflects the thymic productivity . RET of T cells is quantifying by measurement of T cell receptor (TCR) rearrangement excision circles (TRECs) .…”
Section: Introductionmentioning
confidence: 99%
“…Thymic atrophy reduces repertoire diversity and increases susceptibility to infection 1,2 . In addition, one study has found an association between thymic atrophy and CVD 39 . In another study, anti-thymocyte globulin increases the incidence of CVD when administered to patients receiving renal transplantation 40 .…”
Section: Discussionmentioning
confidence: 99%